Effects of parenting quality on adolescents' personality resemblance to their parents. The TRAILS study. (August 2016) - Langenhof, M. Rohaa; Komdeur, Jan; Oldehinkel, Albertine J.
Abstract: This study considers the development of resemblance between 741 adolescents and their biological parents, across six NEO-PI-R personality traits known to be important in psychological problems: anger-hostility, impulsiveness, vulnerability, assertiveness, excitement-seeking, and self-discipline. We modelled the association between perceived parental warmth and rejection at age eleven and personality resemblance to parents at about age sixteen. Parenting experienced during early adolescence was related to the degree and direction in which adolescents resembled their parents five years later in life. Rejection, especially from fathers, significantly predicted a smaller resemblance to both the parents. Girls were more strongly affected by parental quality than boys, and there was some indication that adolescents responded in opposite ways to parenting from mothers and fathers. This study is a first step in uncovering the complex interplay between parenting, gender, and the current generation's ability to develop personality traits independent from the previous generation.